What are the development priorities for management of type 2 diabetes by general practitioners in Ningbo, China: a qualitative study of patients’ and practitioners’ perspectives - Woolley, Angharad; Li, Li; Solomon, Josie; Li, Jialin; Huang, Kai; Chahal, Punam; Chahal, Priya; Tu, Gloria; Chahal, Pritpal; Chattopadhyay, Kaushik (2020)
Objectives To explore patients’ and general practitioners’ (GPs’) perspectives on primary care management of patients with type 2 diabetes mellitus (T2DM) in Ningbo, China. We aimed to understand the current benefits and challenges and to identify development priorities. Design Exploratory qualitative descriptive study using face-to-face interviews and analysed by thematic, inductive analysis. Setting 11 primary care facilities spread across the city of Ningbo, China. Participants 23 patients with T2DM and 20 GPs involved in caring for patients with T2DM. Results GPs were considered the first point of contact and providers of information. However, the care varied, and many GPs lacked confidence and felt overworked. The medication was a particularly weak area. The diagnostic screening commenced late, leading to crisis presentations. Patients were variably informed about their condition, contributing to poor adherence. Conclusions Future developments of primary care for T2DM in Ningbo should centre around improving GP confidence and workload and patient education and adherence.